L’étudiant déficient visuel dans l’enseignement supérieur : ses rapports à l’institution, ses relations avec les enseignants et ses pairs - Véronique Carrière (Éducation et Socialisation)
This research is interested in students with visual disabilities inclusion since the law « 2005» about equal opportunity. More specifically, we are interested in their relationship with the institution, theirs peers and theirs teachers. The results indicate that even if this law, by the creation of disabled student services office, facilitates the relationship with the institution, the social handicap representations can influence the relationships between the persons. These representations, impregnated by stereotypes, can constitute a difficulty in their inclusion with their non-disabled peers as well as a feeling of faintness in their relationship with their teachers. Therefore, communication difficulties can lead to impeding request for adaptation required to access to the educational resources.